2018
DOI: 10.1016/j.celrep.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a Nucleoside Analog Promotes Cancer Cell Death in a Telomerase-Dependent Manner

Abstract: SUMMARY Telomerase, the end-replication enzyme, is reactivated in malignant cancers to drive cellular immortality. While this distinction makes telomerase an attractive target for anti-cancer therapies, most approaches for inhibiting its activity have been clinically ineffective. As opposed to inhibiting telomerase, we use its activity to selectively promote cytotoxicity in cancer cells. We show that several nucleotide analogs, including 5-fluoro-2′-deoxyuridine (5-FdU) triphosphate, are effectively incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
(63 reference statements)
1
32
0
Order By: Relevance
“…Many telomerase inhibitors has thus been developed to treat cancers; however, none of them becomes the applicable clinical drugs due to their side effects [59][60][61]. On the other hand, a recent study indicated that the telomeric DNA damage could promote cancer cell death [62]. Therefore, we targeted telomere DNA to induce cancer cell death by Nage vector in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Many telomerase inhibitors has thus been developed to treat cancers; however, none of them becomes the applicable clinical drugs due to their side effects [59][60][61]. On the other hand, a recent study indicated that the telomeric DNA damage could promote cancer cell death [62]. Therefore, we targeted telomere DNA to induce cancer cell death by Nage vector in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Human telomerase is a ribonucleoprotein complex with an endogenous RNA template, which catalyzes the extension of hexamer DNA repeats . In a majority of human cancers, telomerase is upregulated or reactivated, which leads to indefinite proliferation of cancer cells . Telomerase is now a critical marker for early diagnosis of cancer .…”
Section: Methodsmentioning
confidence: 99%
“…Our approach centers on the ability of telomerase to misincorporate toxic nucleoside analogs, specifically 5-fluoro-2ʹdeoxyuridine (5-FdU), into telomeric DNA thereby compromising telomere integrity to induce cell death (Figure 1). 5 This mechanism of telomerase-dependent misincorporation leads to a disruption of binding interactions at the telomere essential for maintaining telomere stability. 5 The loss of essential protein-DNA complexes at compromised telomeres initiates illicit DNA damage response and eventual cell death in a telomerase-dependent manner.…”
mentioning
confidence: 99%
“…5 This mechanism of telomerase-dependent misincorporation leads to a disruption of binding interactions at the telomere essential for maintaining telomere stability. 5 The loss of essential protein-DNA complexes at compromised telomeres initiates illicit DNA damage response and eventual cell death in a telomerase-dependent manner. 5 The expansion of telomeric-based inhibitors to include "Trojan horse" therapeutics provides a resolution for the disadvantages associated with conventional approaches to telomerase inhibition.…”
mentioning
confidence: 99%
See 1 more Smart Citation